2018
DOI: 10.5055/jom.2010.0021
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of acute heroin overdose requiring intensive care unit admission

Abstract: Background: Heroin use carries a large burden of morbidity and mortality. Heroin overdose and in particular events that need intensive care unit (ICU) admission have not been widely examined. The aim of this study was to describe the causes of ICU admission and the outcome of patients with a heroin overdose.Methods: A retrospective chart review of all patients with a heroin overdose admitted to the ICU between 1987 and 2006 was conducted.Results: Forty-two records were available for review. The average age of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…A potential link between opioid overdose and encephalopathy has been reported in case reports and case series 3 5 7–19. Additionally, a prospective observational study reported that 1 of 573 patients visiting the emergency department for opioid overdose suffered from cerebral anoxia, ARDS and death,4 and a retrospective chart review reported that 2 of 42 ICU patients with heroin overdose suffered from anoxemic encephalopathy and death 6. Our finding that 77 (3%) of 2554 admissions related to accidental overdose included a diagnosis of encephalopathy provides additional data on this association.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A potential link between opioid overdose and encephalopathy has been reported in case reports and case series 3 5 7–19. Additionally, a prospective observational study reported that 1 of 573 patients visiting the emergency department for opioid overdose suffered from cerebral anoxia, ARDS and death,4 and a retrospective chart review reported that 2 of 42 ICU patients with heroin overdose suffered from anoxemic encephalopathy and death 6. Our finding that 77 (3%) of 2554 admissions related to accidental overdose included a diagnosis of encephalopathy provides additional data on this association.…”
Section: Discussionmentioning
confidence: 98%
“…We included both anoxic brain damage and toxic encephalopathy in the definition of encephalopathy in our study, because case reports raise concerns about a potential association between opioid overdose about these outcomes, and these diagnoses describe important brain injuries 6–9. In addition, studies that use administrative health data face the limitation that coding of outcomes in the data will often not be precise, so we have included unspecified encephalopathy in the outcome definition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The types of organ dysfunction among sepsis patients with and without opioid-related hospitalizations were similar, with the notable exception of higher rates of respiratory failure requiring mechanical ventilation in the opioid-related hospitalization group. Respiratory failure is a known source of morbidity and mortality associated with opioid overdose, typically due to direct respiratory suppression, aspiration, acute lung injury, and/or septic emboli (37, 38).…”
Section: Discussionmentioning
confidence: 99%